2010
DOI: 10.1200/jco.2009.23.3452
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of KRAS and BRAF in Stage II and III Resected Colon Cancer: Results of the Translational Study on the PETACC-3, EORTC 40993, SAKK 60-00 Trial

Abstract: In stage II-III colon cancer, the KRAS mutation status does not have major prognostic value. BRAF is prognostic for OS in MS-L/S tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

86
874
14
29

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,077 publications
(1,003 citation statements)
references
References 34 publications
86
874
14
29
Order By: Relevance
“…Larger studies are therefore required in order to confirm whether a specific KRAS mutation might lead to a clinically relevant prognostic effect in patients with CRC. 35 …”
Section: Prognostic Role Of Kras Gene Mutationsmentioning
confidence: 99%
“…Larger studies are therefore required in order to confirm whether a specific KRAS mutation might lead to a clinically relevant prognostic effect in patients with CRC. 35 …”
Section: Prognostic Role Of Kras Gene Mutationsmentioning
confidence: 99%
“…2. Prognosis -Several studies have shown dMMR CRC has a better prognosis than MMR proficient (pMMR) CRC Guastadisegni et al, 2010;Klingbiel et al, 2015;Popat et al, 2005;Roth et al, 2010;Sinicrope et al, 2015). MSI tumours are less prone to lymph node (Mohan et al, 2016) and synchronous liver metastasis (Nordholm-Carstensen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, KRAS mutation has been associated with poor CRC prognosis in the QUASAR trial (1,583 patients) ( 24 ) and the RASCALII study (3,439 patients, stages II -IV) ( 25 ). In contrast, the PETACC-3 trial (1,564 patients, stages II and III) found no evidence for association of KRAS mutation with relapse-free survival or overall survival ( 26 ). Overall, the data are inconclusive as regards an association between KRAS and CRC prognosis, and a recent meta-analysis covering studies published between 1992 and 2011 showed no overall association ( 23 ).…”
Section: Introductionmentioning
confidence: 99%